The Influence of the Farmers Knowledge Level toward the Ettawa Goat Reproduction Regulation System at Ranojaya, Indonesia - Hamdan Miftahuddin; H. Hastuti (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2017)
This research was conducted from May to June of 2016 in Ranojaya, Indonesia. There was so the purpose of this research is to find out how much influence the farmers’ knowledge level toward the Ettawa goat reproduction regulation system in Ranojaya, Indonesia. In determining the location of the research, the researchers were deliberately placed in Ranojaya, Indonesia. It wasby looking at the stressing of Ranojaya area.It was found thatmost of the community have business of Ettawa goat. The technique of determining the sample using purposive sampling technique, where the samples are deliberately selected from a population on the basis of the criteria determined by the researcher is the breeder of Ettawa goat who knows about the regulation of the reproductive system, and from the 1,193 population of 15 selected farmers as the sample/respondent. The results showed that (1) There was a significant correlation between knowledge level of farmer with reproduction system arrangement on an Ettawa goat in Ranojaya, Indonesia. (2) The correlation coefficient between variable X1 (number of livestock ownership) to variable Y is 0.75. This means that there is a strong relationship between the factor of the number of livestock owned on the knowledge level of the farmers with the regulation of reproduction system in Ettawa goat cattle. (3) The correlation coefficient between variables X2 (long breeding) to variable Y is 0.64. This means that there is a strong relationship between the old factors of breeding to the level of knowledge of farmers with the regulation of reproduction system on livestock Ettawa goat. (4) The result of program effectiveness calculation and the effectiveness of the increase of respondent knowledge about the reproduction system regulation on Ettawa crossbreed goat got the effective result, namely 72,75%. While the increase of knowledge of respondents got an effective result that is 47.5%, or there is an increase in knowledge of the respondents after having been done illumination was 14.87%